2003 Linnedalen Main Weather Station Data - (:unkn) unknown (My University, 2009)
2003 Meteorological data from the Main Weather station in the Linne Valley (78.02710 N, 13.85025 E, 25m elev ASL). The station is an Onset data logger H21-001 and Onset sensors (see http://www.onsetcomp.com). The station records data every 30 minutes.
Keywords: Meteorological data; Main Station